Characteristics and Comorbidities Influencing Mortality Risk Among Hereditary Angioedema Patients - Subhan Khalid; Alan T. Hitch (Journal of Health Economics and Outcomes Research)
# Background Patients with hereditary angioedema (HA) face a heightened mortality risk due to multiple factors.